GENDER DIFFERENCES IN HIGH ACHIEVERS' ATTRIBUTIONAL STYLE - NICOLETA LAURA POPA (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. The present study focuses on variations in attributional style among high achieving adolescents, in relation with gender and level of achievement. The sample included 113 Romanian high school students, who completed an adapted version of Attributional Style Questionnaire (ASQ). Results suggest that gifted girls tend to display an internal, stable and global attributional style, which leads to a self-effacing attributional pattern. High achieving boys show similar attribution patterns, with a more positive tendency. Although differences among the four subgroups are inconsistent, the findings suggest a disadvantaging attributional style in both high achieving boys and high achieving girls.